Economic assessment of aseptic compounding rooms in hospital pharmacies in five European countries. (April 2015) - Dekyndt, Bérengère; Décaudin, Bertrand; Lannoy, Damien; Odou, Pascal
Purpose: The aims of the study are to make an inventory of fixtures of aseptic compounding structures, to compare, using real examples, the design and operating costs of controlled atmosphere area (CAA) with isolators and CAA with laminar flow biological safety cabinets (BSCs) in order to determine the most economical scheme in hospitals and to give a final facilities cost calculated for one workstation. Methods: Forty-three hospitals were interviewed (21 French and 22 from four European countries) over seven months. Hospital pharmacists completed a form with 390 items. Hospitals are compared according to their workstation type: BSCII or BSCIII (group B) and isolator (group I), using Mann and Whitney's statistical test and Monte-Carlo modeling. Results: Twenty-one hospitals responded (11 French and 10 from other European countries). All European compounding unit organizations are not significantly different. The study compared items such as infrastructure cost, equipment cost, staff cost, consumable cost, cleaning cost and control cost. A synthesis of all costs has been drafted to calculate an estimated preparation cost which seemed to be higher for group B than for group I when staff costs were included ($46 and $31, respectively, in study conditions). Conclusions: The different costs studied have revealed little significant difference between group B and I. The preparation cost in group B appears higher than in group I. This pilot study has resulted in the calculation of an estimated manufactured preparation cost but this work should be completed to help optimize resources and save money.